Sydenham Chorea On Indonesian 10 Years Old Boy Caused By Rheumatic Heart Disease : Case Report And Literature Review - Irfana, Laily; Airlangga, M. Perdana; Indrawati, Nina Devi; Mahyuddin, M. Hanun (Jurnal Ilmu Kesehatan dan Kesehatan, 2022)
Sydenham's chorea (SC) is one of the manifestations of rheumatic fever, and is the most common cause of chorea in childrens. Sydenham chorea is characterized by involuntary movements such as jerking of the arms, legs, and face. The following case is a 10-year-old boy with complaints of moving his right arm and leg on its own. On physical examination, there was a grade 4/5 systolic murmur at ICS 5 2 cm lateral to the left MCL blowing radiating to the left arm. ASTO examination there is an increase. CT scan of the head without contrast showed no abnormalities. The results of echocardiography showed severe mitral regurgitation. The patient was diagnosed with Sydenham Chorea and Rheumatic Heart Disease. The patient refused hospitalization and was treated as an outpatient with given therapy erythromycin 250 mg four times daily for 10 days followed by a twice daily dose for the next two months, symptomatic haloperidol 1 mg and trihexyphenidyl 0.5 mg twice a day, aspirin 300 mg four times a day for one month. From this treatment, the complaints improved slowly, and the chorea disappeared within 10 days of the start of treatment.